RETRACTED: Description, typology and types of PR texts by genre (in the example of Uzbek information services) - Malikova Guzal; Komilova Zarina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001